Study on the Permeability Characteristics of Polyurethane Soil Stabilizer Reinforced Sand - Jin Liu; Xiaohui Qi; Da Zhang; Qiao Feng; Yong Wang; Debi Prasanna Kanungo (Advances in Materials Science and Engineering)
A polymer material of polyurethane soil stabilizer (PSS) is used to reinforce the sand. To understand the permeability characteristics of PSS reinforced sand, a series of reinforcement layer form test, single-hole permeability test, and porous permeability test of sand reinforced with PSS have been performed. Reinforcement mechanism is discussed with scanning electron microscope images. The results indicated that the permeability resistance of sand reinforced with polyurethane soil stabilizer is improved through the formation of reinforcement layer on the sand surface. The thickness and complete degree of the reinforcement layer increase with the increasing of curing time and PSS concentration. The water flow rate decreases with the increasing of curing time or PSS concentration. The permeability coefficient decreases with the increasing of curing time and PSS concentration and increases with the increasing of depth in specimen. PSS fills up the voids of sand and adsorbs on the surface of sand particle to reduce or block the flowing channels of water to improve the permeability resistance of sand. The results can be applied as the reference for chemical reinforcement sandy soil engineering, especially for surface protection of embankment, slope, and landfill.